UMUR SIMPAN TELUR AYAM YANG DILAPISI DENGAN KAPUR (CaCO3) DAN MINYAK KELAPA - Mudawaroch, Roisu Eny (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2024)
Preservation of fresh eggs can be done by coating the centipede with coating material. The purpose of this study was to determine the physical quality of chicken eggs treated with centipede coating and shelf life at room temperature. The ingredients used are purebred chicken eggs, coconut oil and chalk. The parameters observed are: Egg weight, egg index, egg white index, yolk index, egg white pH, yolk pH, egg color. The study design is a complete randomized design of factorial patterns. The results showed that the type of egg centipede coating material and shelf life showed a marked difference in egg weight. The coating material and shelf life have no effect on the egg index. The treatment of centipede coating material has a very noticeable effect on the egg white index and egg yolk index. The treatment of centipede coating material and shelf life have a significant influence on the pH value of egg white and egg yolk pH. The color of the yolk of purebred chickens with the treatment of centipede coating materials and the length of storage at room temperature has a noticeable effect on the color of the yolk. The conclusion that the coating of the egg centipede using chalk and coconut oil and shelf life showed a marked difference in egg weight, egg white index, yolk index, white pH, yolk pH and egg color, while the egg index did not differ markedly.